Analysis Of Potential Hazards And Use Of Personal Protection Equipment (PPE) On Oil Palm Processing And Production Workers In PKS XYZ - novita eka rini, willia; Yolanda Gustina Pane; Budi Aswin; La Ode Reskiaddin (CV. AFDIFAL MAJU BERKAH, 2022)
Every workplace has a risk of work accidents. Potential hazards and risks in the workplace can occur due to work systems or work processes that are not in accordance with procedures, the use of machines, tools and materials that are not careful, the behavior of workers, as well as the work environment itself which will have an impact on reducing the effectiveness of workers. The purpose of this study was to determine the potential hazards and use of personal protective equipment (PPE) in PKS XYZ. This research uses a descriptive qualitative research type. The research informants were determined using purposive sampling, totaling 13 informants consisting of 3 key informants, 7 main informants and 3 supporting informants. Data collection techniques were carried out by in-depth interviews, observation, and documentation. Test the validity of the data using triangulation techniques. The research results obtained in the palm oil processing and production section at PKS XYZ contained 51 potential hazards spread over 7 work stations which were classified into 5 sources of danger including mechanical hazards, physical hazards, chemical hazards, electrical hazards, and ergonomic hazards. So it is necessary to have support from the company to implement an Occupational Safety and Health management system in factories and require workers to use personal protective equipment while working.